Relative age effect in sport: comment on Alburquerque, et al. (2012) - Gonzalez-Villora, S.; Pastor Vicedo, J. C. (Perceptual and Motor Skills, 2012)
Relative age effect (RAE) describes the long-lived performance effects associated with systematic age differences of athletes in sports where competition is organized according to age cohorts. This phenomenon has been studied in many different sports, across widely varying samples and other factors such as anthropometric and fitness characteristics, career stage, competition or selection level, cultural-societal trends, elite participation, gender, laterality, leadership development, in performance achievement and participation rates, in success and dropout, player nationality, playing position or self-selection. The relative age effect is not independent of other important factors, such as birthplace, gender, professional/amateur sport, or family socioeconomic factors. Most studies have looked at the advantage in performance that athletes who were born near the end of the year have, because they are relatively older and more developed than those in their competition cohort who have birthdays earlier in the year. RAEs of different magnitudes have been found depending on factors such as sex (males show larger effects than women) and type of sport (professional and majority sports have larger effects than amateur and minor sports). For these reasons the effect is regarded as a significant influence in the development of athletes' careers, and the acquisition of sports skills. The present article briefly summarizes evidence that may help explain how RAE influences the maintenance and development of sport expertise. (Comment on: http://doi.org/10.2466/05.25.PMS.114.2.461-468 )